Pendampingan Program Tahfizul Qur’an Menggunakan Metode Tasmi’ dan Muraja’ah di SMP Negeri 4 Padang Panjang - Dari, Yuni Wulan; Kustati, Martin; Gusmirawati, Gusmirawati; Amelia, Rezki (Universitas Islam Internasional Darullughah Wadda'wah, 2024)
This mentoring activity aims to improve students' ability to memorize the Qur'an using the Tasmi' and Muraja'ah methods at SMP Negeri 4 Padang Panjang through the Tahfidzul Qur'an program which is carried out once a week after school hours are finished.. Implementing the Tahfidzul Qur'an program is crucial to cultivate a generation of proficient Qur'anic memorizers. SMP Negeri 4 Padang Panjang faces various challenges in memorizing the Qur'an. However, despite these challenges, there are still students who are motivated and curious about the process of memorizing the Qur'an. This is what motivates SMP Negeri 4 Padang Panjang to implement the tahfizul Qur'an program once a week at school, utilizing the Muraja’ah and Tasmi’ methods to maintain and facilitate students' memorization of the Qur'an. The service learning method serves as the implementation method for this mentoring program. The results of this activity show that students are able to memorize the Qur'an well and apply it for further memorization using the Tasmi’ and Muraja’ah methods.